Cu-Sn-S system: Vibrational properties and coexistence of the Cu2SnS3, Cu3SnS4 and Cu4SnS4 compounds. (September 2020) - Guc, Maxim; Oliva, Florian; Fairbrother, Andrew; Jawhari, Tariq; Alcobe, Xavier; Placidi, Marcel; Pérez-Rodríguez, Alejandro; Saucedo, Edgardo; Izquierdo-Roca, Victor
Abstract: In the present study the transformation between Cu2 SnS3, Cu3 SnS4 and Cu4 SnS4 compounds is analyzed by means of X-ray diffraction and Raman scattering spectroscopy. A detailed analysis of the X-ray diffractograms showed the dependence of formation of the indicated compositional phases from the [Cu]/[Sn] ratio, which was also correlated with the evolution of the Raman spectra. The results are complemented with the detailed analysis of microscopic Raman imaging. Finally, fingerprint Raman spectrum for each compositional polymorph is presented, which should exclude any misinterpretations during phase analysis in future works. Graphical abstract: Image, graphical abstract